Zola v Ljubljanskem zvonu - Smolej, Tone (Primerjalna književnost, 2004)
Zola in Ljubljanski zvon (1881-1890). The article researches the early Slovenian reproductive (critical) reception of Émile Zola in the first decade of the Ljubljanski zvon magazine. It examines how the French author is referred to and reviewed in articles by F. Celestin, K. Štrekelj, J. Stritar, F. Svetič and J. Kersnik, and makes comparisons to certain articles by German authors (R. Kaufmann, T. Zolling).
Keywords: Zola, Emile, 1840-1902; francoska književnost; French literature; naturalizem; literarna recepcija; slovenska literarna kritika; Ljubljanski zvon